(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
There is an unparallel demand for housing in most of the countries due to rapid urbanizationand a rise in population across the globe. Government agencies are playing a pivotal role in striking thebalance between supply and demand through various policy interventions. Despite several initiatives andreforms, the supply and demand mismatch has not narrowed significantly. One of the key factorsidentified for the slow delivery of housing projects is the use of conventional technology forconstruction.In the 1980s 1990s, countries like Malaysia, Singapore, Hong Kong, China, and Dubai, among others,recognized the need for a paradigm shift from conventional to precast or industrialized constructionsystems and established various long-term plansroad maps for the implementation of this technology inthe housing sector. With decades of strategic planning and a committed approach, many of thesecountries have showcased successful implementation of housing projects using this technology. India isalso looking forward to spreading the application of precast and other offsite construction technologiesfor housing projects through various government schemes. The paper reviews the influence of thesegovernment interventions and incentives on the adoption of precast technology in the housing segmentthrough a systematic literature review.